Expert product management toolkit bundle : advanced techniques, tips, strategies, templates and training for product management & product marketing - Lawley, Brian (HappyAbout.info, 2008)
The Expert Product Management Toolkit Bundle includes all of the templates, knowledge, training and information that you need to make your products more successful. It includes the book Expert Product Management: Advanced techniques, tips and strategies for Product Management and Product Marketing as well as four of the 280 Group Product Management Toolkits (Product Roadmaps, Launches, Beta Programs & Product Reviews). All of the examples, plans and documents discussed that are covered in the book (and much more) are included in MS Office format (Word, Excel & Powerpoint) for a total of 124 templates, four narrated on-demand training presentations, samples, examples and white papers.